The Effectiveness of Using the Anthropometric Stunting Meter in Children Aged 24-59 Months at the Lageun Health Center, Aceh Jaya District - Lensoni Lensoni; Elmiyati Elmiyati; Yulinar Yulinar; M. Yahya; Ulfa Hanum (Jurnal Penelitian Pendidikan IPA, 2023)
Stunting in toddlers can have an impact on children's health and intelligence in the future, such as susceptibility to infection and decreased performance in school. This activity aims to train posyandu cadres in improving anthropometric measurement skills in toddlers. The target audience for this community service activity is posyandu cadres. Stunting indicates chronic nutritional problems as a result of long-lasting man many factors increase stunting in toddlers, both directly and indirectly. The purpose of this study was to determine the effectiveness of the stunting anthropometric tool in children aged 24-59 months in the working area of the Lageun Health Center. The population in this study were all toddlers aged 24-59 months, totaling 45 toddlers. The number of samples is 22 toddlers. The purpose of this training activity is to increase awareness of the targeted skills in independent early detection of stunting using anthropometric methods. The method of implementing this community service activity uses a combination of education, training, and simulation methods. The targets are pregnant women, mothers with children under five years old, and health cadres. Based on field studies, the stunting anthropometric tool shows effective results. The results of the implementation of activities show high enthusiasm from the target. It is hoped that this activity can parents' awareness of toddlers' nutritional health problems, so that t has an impact and can contribute to reducing the number of stunting cases to be precise in the Lageun Health Center area.